Cultural Identity of Attack On Titan Fans on Social Media Twitter in Indonesia - Tyara Maulidia Irwana; Daniel Hermawan (Universitas Diponegoro, 2022)
Research that carries the theme of cultural identity is always associated with identities that are formed and seen from ethnicity, race, country, and the like. The purpose of this study is to reveal the cultural identity of fans in an internet-based fandom, especially on Twitter social media. The theories used are Hall and Barker's theory of cultural identity, Nagy-Koles' virtual identity theory, Jenkins' fan study, and McQuail's new media theory. The approach used to conduct this research is a qualitative approach, while the method used to conduct this research is participatory observation and interview that involved several fans that followed one of the Attacks on Titan’s fandom accounts, AOTFESS. In AOTFESS, the study later found out that their cultural identity is not always seen from literal symbols, but rather formed and then found through the interactivities of fans who follow the account. <a href=